(untitled) (Baghdad Science Journal, 2012)
Results showed high efficiency of the predator Chrysoperla carnea (Stephens) to attack and consume nymphal instars and adults of cabbage aphid, Brevicoryne brassicae (L.).The total average of the nymphal instars consumed by the larval stage of predator were 308.67, 285.9, 198.77, 154.7 for 1st ,2nd ,3rd ,4th nymphal instars respectively .While it was 110,107.9 for apterae and alatae respectively . Also, predation efficiency increases with the progress of the larval instars up to the third (last) which was the most voracious .The 1st instar nymph consumed by the larvae of the predator were 47,80,181.67 nymphs ,with predation rate of 14.71% , 23.75% and 50.13% for 1st ,2nd and 3rd larval instars